Integer Powers of Anti-Bidiagonal Hankel Matrices - Silva, João Lita da (2019)
In this paper we derive a general expression for integer powers of real upper and lower anti-bidiagonal matrices with constant anti-diagonals using Chebyshev polynomials. An explicit formula for the inverse of these matrices is also provided.